MANAJEMEN SDM DALAM MENINGKATKAN EDUCATOR FUNCTIONS - Trisna; Thajusubki, Maki (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2024)
Abstract : This research discusses human resource management in improving the function of teaching staff at MTs Negri 1 Mjalengka. The research method used is a qualitative field study method. The research results show that human resource management in improving the function of teaching staff at MTs Negri 1 Majalengka includes planning, organizing, implementing and supervising. Planning is carried out carefully, through deliberations between school leadership and supervisors and educators, organizing is carried out by coordinating the implementation of human resource management in improving the function of teaching staff and an organizational structure that describes the working relationships of all school members, supervision is carried out in two ways, including supervision carried out by external and internal parties. For external supervision, supervision is carried out by inspectors from the education service. When there are deficiencies, supervisors will work together to find solutions. Meanwhile, internal supervision is carried out by the school principal so that various problems are related to human resource management. Abstrak : Penelitian ini membahas mengenai manajemen sumber daya manusia dalam meningkatkan fungsi tenaga pendidik di MTs Negri 1 Mjalengka. Metode penelitian yang digunakan yaitu metode kualitatif studi lapangan. Adapun pada hasil penelitian menunjukan bahwa Manajemen sumber daya manusia dalam meningkatkan fungsi tenaga pendidik di MTs Negri 1 Majalengka meliputi dari perencanaan, pengorganisasian, pelaksanaan, dan pengawasan. Perencanaan dilakukan secara cermat, melalui musyawarah pempinan sekolah dan pengawas serta pendidik, pengorganisasian dilakukan dengan adanya pengkordinasian dalam melaksanakan manajemen sumberdaya manusia dalam meningkatkan fungsi tenaga pendidik dan struktur oeganisasi yang menggambarkan hubungan kerja semua warga sekolah, pengwasan ada dua hal yang dilakukan diantaranya pengawasan yang dilakukan oleh pihak eksternal dan internal. Untuk eksternal, pengwasan dilakukan oleh penilik dari dinas pendidikan, ketika ada kekurangan maka pengawas akan bersama-sama untuk mencari solusi. Sedangkan pengawasan secara internal dilakukan oleh kepala sekolah sehingga berbagai persoalan terkait dengan manajemen sumber daya manusia.